Corporate Governance Transparency and Board Independence: The Case of Four European Emerging Countries - Ruxandra-Adriana Mateescu (Journal of Accounting and Management Information Systems (JAMIS), 2015)
This paper investigates the influence that an independently structured board exerts over implementing sound financial and non-financial disclosure mechanisms (especially regarding corporate governance mechanisms) in listed companies from four European emerging countries (Estonia, Poland, Hungary and Romania). Previous studies have shown that they usually trust more public disclosed information than the internal reports they have access to. This study brings evidence that in most cases the companies in the sample comply with the independence requirements. Regarding the boards' size, larger companies appoint more directors and larger audit committees. Finally, the study demonstrates that companies with larger audit committees disclose more financial and non-financial information.
Keywords: G32; G34; 650; transparency; corporate governance; emerging countries; board independence; audit committee